Competitiveness, Sustainability and Diversification on Atlantic Coast of Iberian Peninsula: Local Management of the European Fisheries Fund (2007-2013). - Felicidades-García, Jesús; Piñeiro-Antelo, María de los Ángeles (Revista de Estudios Andaluces, 2017)
The incorporation of the territorial perspective into the Common Fisheries Policy (CFP), through the delimitation of fishing areas and the creation of Fishery Local Action Groups (FLAGs), has allowed the decentralized management Axis 4 of the European Fisheries Fund (EFF) through the application of the LEADER method in this sectoral policy. The present study brings together the research of five case study regions (including Portugal) and their FLAGs in the period 2007-2013. Based on the analysis of each participatory local development strategy (LDS) and measures financed, there are different responses to the experience: misalignment and lack of cohesion between projects, excessive dependence on local power, and, in contrast, very meritorious actions and impact both in the fisheries sector and in the sustainable development of the coastal communities.